ANALYSIS OF COMMUNITY SATISFACTION WITH THE QUALITY OF PUBLIC ADMINISTRATION SERVICES AND GOVERNMENT PERFORMANCE IN MEDAN CITY - Natalia ET Sihombing (The American Journal of Interdisciplinary Innovations and Research, 2024)
The aim of this research is to determine and analyze the extent to which the variables of accountability and transparency, reliability in service ( reliability ), and responsiveness in responding to customer complaints (responsiveness ) influence the performance of the Medan City Government through community satisfaction as an intervening variable . The subjects of this research are the residents/society of Medan City, where the variables in this research are independent variables, namely transparency and accountability, reliability and responsiveness , the dependent variable, namely the performance variable of the Medan City Government and the intervening variable is the satisfaction variable of the people of Medan City . The results of data analysis used SEM analysis using SMART PLS 4.0 software . Method research using descriptive quantitative data analysis methods using the structural equation model (SEM) method, where the results of data processing using the SEM method are carried out using the PLS 4.0 application . From the results of this research, the conclusions are that partially the variables of transparency and accountability, reliability and responsiveness influence the performance of the Medan City Government and influence the satisfaction of the people of Medan City. Simultaneously, the variables of transparency and accountability, reliability and responsiveness influence the performance of the Medan City Government through the variable satisfaction of the people of Medan City as an intervening variable . The more transparent and accountable you are, the more you are able to improve the quality of services provided to the community and the more you are able to respond to responses and complaints from the community, this will directly improve the performance of Government officials on an ongoing basis, where good performance from Government officials will indirectly improve the performance of the Government, as well as will increase public satisfaction in continuing to use these government services to take care of all public administration needs.